Game‐theoretic energy trading network topology control for electric vehicles in mobile smart grid. Issue 4 (1st July 2015) - Mondal, Ayan; Misra, Sudip
Abstract : Existing works on energy trading consider different schemes for forming energy trading networks, which assume that each plug‐in hybrid electric vehicle (PHEV) is connected with a single micro‐grid. Consequently, in on‐peak hours, a PHEV obtains the requested energy during the allotted time slot by paying a higher price. Alternatively, the PHEV waits for a significant duration of time to get serviced until the on‐peak hour elapses. In this study, the authors propose that a PHEV may obtain energy from any of the available micro‐grids within a coalition instantaneously without paying higher price. In this work, the problem of energy trading network topology control (ENTRANT) for PHEVs is studied as a 'multi‐leader multi‐follower Stackelberg game'. In this game, each PHEV acts as a leader, and decides the amount of energy to be requested to the selected micro‐grid. On the other hand, the micro‐grids act as followers, need to decide the price per unit energy. Using variational inequality, it is shown that the proposed scheme, ENTRANT, has generalised Nash equilibrium, which is also socially optimal. ENTRANT enables the PHEVs and the micro‐grids within a coalition to reach the equilibrium state, is evaluated theoretically, as well as through simulations.